Dampak Sosial Penggunaan Kayu Bakar Pada Oven Tembakau terhadap Kesehatan Masyarakat di Desa Batu Nampar Kecamatan Jerowaru Lombok Timur: Social Impact of Using Firewood in Tobacco Ovens on Public Health in Batu Nampar Village, Jerowaru District, East Lombok Regency - Ahmad Salman Alparizi (Pendidikan Al-Gafari, 2025)
Tobacco ovens have various fuels, ranging from kerosene, coal to firewood. Each fuel used in tobacco ovens is selected based on the results and price of the fuel. Tobacco oven owners never think about the impact it has on the environment and the surrounding community. Therefore, the purpose of this study is focused on the social impact of the use of firewood in tobacco ovens on public health in Batu Nampar Village, Jerowaru District, East Lombok Regency. The research method used in this study is descriptive research with a qualitative research approach. Data collection techniques in this study are observation, interview and documentation techniques with descriptive-qualitative data analysis techniques. The results of this study are factors that cause the use of firewood in tobacco ovens, including the price of kerosene or coal is too high (expensive), rare and risky, firewood is cheaper and easier to obtain from local residents and the quality of tobacco from tobacco ovens with firewood is better when compared to coal. Meanwhile, the work of tobacco oven workers is increasing and more because they are required to maintain the temperature of the tobacco oven for 3-4 days, the smoke from the tobacco oven that uses firewood is more and thicker so that it can cause air pollution in the environment around the tobacco oven, ash from the remaining combustion in the tobacco oven can cause dust that interferes with vision and the air becomes hotter especially in the tobacco oven environment.